Attenuation effect of Abnormal Savda Munziq on liver and heart toxicity caused by chemotherapy in mice - AIKEMU, AINIWAER (Exp Ther Med, 2016)
Abnormal Savda Munziq (ASMq), an Uighur medicine formula commonly used in the treatment of cancer, has been speculated to possess antioxidative and antiproliferative effects, and to regulate immune activity. The present study was designed to systematically elucidate the toxicity-reducing activity of ASMq in mice undergoing combination chemotherapy with doxorubicin and 5-fluorouracil (5-FU). The mice were divided into normal (saline, 10 ml/kg) and doxorubicin + 5-FU groups (doxorubicin, 2.5 mg/kg; 5-FU, 10 mg/kg on alternate days). In addition, three groups received different doses of ASMq (2, 4 and 8 g/kg), in addition to doxorubicin (2.5 mg/kg) and 5-FU (10 mg/kg) treatment on alternate days. The histology of the heart and liver, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) activity, malondialdehyde (MDA) concentrations in heart homogenate, and various biochemical parameters of the liver were evaluated. Compared with the normal control group, ASMq dose-dependently improved a number of variables, including body weight, liver index, transaminase and total protein, and partially normalized liver and cardiac pathology. ASMq restored activities of defense antioxidant enzymes SOD and GSH-Px towards normal levels, and decreased MDA concentration in dose-dependent manner. These results demonstrated that ASMq provides significant protection against doxorubicin + 5-FU combination induced hepatotoxicity and cardiotoxicity. Further studies are required to determine the effects of ASMq against doxorubicin + 5-FU-induced toxicity during chemotherapy in vivo.